T Cells Subsets in the Immunopathology and Treatment of Sjogren’s Syndrome - William de Jesús Ríos-Ríos; Sorely Adelina Sosa-Luis; Honorio Torres-Aguilar (Biomolecules, 2020)
Sjogren’s syndrome (SS) is an autoimmune disease whose pathogenesis is characterized by an exacerbated T cell infiltration in exocrine glands, markedly associated to the inflammatory and detrimental features as well as the disease progression. Several helper T cell subsets sequentially converge at different stages of the ailment, becoming involved in specific pathologic roles. Initially, their activated phenotype endows them with high migratory properties and increased pro-inflammatory cytokine secretion in target tissues. Later, the accumulation of immunomodulatory T cells-derived factors, such as IL-17, IFN-γ, or IL-21, preserve the inflammatory environment. These effects favor strong B cell activation, instigating an extrafollicular antibody response in ectopic lymphoid structures mediated by T follicular helper cells (Tfh) and leading to disease progression. Additionally, the memory effector phenotype of CD8+ T cells present in SS patients suggests that the presence of auto-antigen restricted CD8+ T cells might trigger time-dependent and specific immune responses. Regarding the protective roles of traditional regulatory T cells (Treg), uncertain evidence shows decrease or invariable numbers of circulating and infiltrating cells. Nevertheless, an emerging Treg subset named follicular regulatory T cells (Tfr) seems to play a critical protective role owing to their deficiency that enhances SS development. In this review, the authors summarize the current knowledge of T cells subsets contribution to the SS immunopathology, focusing on the cellular and biomolecular properties allowing them to infiltrate and to harm target tissues, and that simultaneously make them key therapeutic targets for SS treatment.